Correlation between reduction of superior interventricular groove epicardial fat thickness and improvement of insulin resistance after weight loss in obese men - Liang, Kae-Woei (Diabetol Metab Syndr, 2014)
BACKGROUND: It has been recognized that reduction of abdominal visceral fat and subcutaneous fat are associated with improvement in insulin-resistance (IR) after weight loss. However, few studies have investigated the correlation of reduction in epicardial adipose tissue (EAT) with improvement of IR index after weight loss in obese non-diabetic men with metabolic syndrome (MetS). METHODS AND RESULTS: We prospectively enrolled 32 non-diabetic men with MetS for a 3-month weight reduction program mainly by diet control and exercise. Magnetic resonance imaging (MRI) examinations were used to measure EAT, subcutaneous fat, and abdominal visceral fat. Anthropometric parameters, oral glucose tolerance test (OGTT), and serum adipokines were assessed before and after the weight loss program. After a 3-month weight loss program, 27 obese MetS men had significant weight loss >5% (97 ± 14 to 87 ± 14 kg, with a 10.7 % decrease, p < 0.001). Multivariate analysis revealed that the decrement ratio of superior interventricular groove (SIVG) EAT thickness (r = 0.322, p = 0.044) and serum leptin (r = 0.626, p < 0.001) significantly correlated with the percentage improvements of fasting HOMA-IR index. Furthermore, the decrement ratio of SIVG EAT thickness (r = −0.370, p = 0.017) and decrement ratio of subcutaneous fat area (r = −0.673, p = 0.006) were significantly correlated with improvement of OGTT-derived Matsuda insulin-sensitivity index. CONCLUSIONS: The decrement ratio of SIVG EAT correlated with improvement of both HOMA-IR and OGTT-derived Matsuda insulin-sensitivity indexes after weight loss in obese non-diabetic men with MetS. CLINICAL TRIAL REGISTRATION: (Multi-faceted Evaluations Following Weight Reduction in Subjects with Metabolic Syndrome NCT 01065753 on Feb 8, 2010).